2022
DOI: 10.31272/jeasd.24.5.5
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Biomedical Applications of Alumina

Abstract: This review presents the composition, structure, mechanical characteristics, and applications of alumina (aluminum oxide) in biomedical. Alumina used for implant manufacturing is either single-crystal sapphires or high density and quality polycrystalline. The major sources of highly-purity alumina are organic corundum and bauxite. Like any other brittle component, polycrystalline alumina's mechanical characteristics are largely dependent on grain size and porosity distribution. It was shown that, due to slowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…As a result, α-alumina implants can undergo loosening and develop fibrosis, also known as fibrous encapsulation. This is a protective mechanism, where fibrous tissue forms to isolate the implant from the biological system, which may lead to complete encapsulation of the implant over time [45]. Therefore, it is reason that the use of pure α-alumina is a big challenge, and the great interest to use alumina is as a base for bioactive composites or as a support for the deposition of bioactive materials [21].…”
Section: Composite With Hydroxyapatitementioning
confidence: 99%
“…As a result, α-alumina implants can undergo loosening and develop fibrosis, also known as fibrous encapsulation. This is a protective mechanism, where fibrous tissue forms to isolate the implant from the biological system, which may lead to complete encapsulation of the implant over time [45]. Therefore, it is reason that the use of pure α-alumina is a big challenge, and the great interest to use alumina is as a base for bioactive composites or as a support for the deposition of bioactive materials [21].…”
Section: Composite With Hydroxyapatitementioning
confidence: 99%
“…Furthermore, alumina is used in construction, fuel cells, abrasive or chemical waste cleaners, microelectronics, etc. In addition to its excessive hardness, electrical resistance, corrosion resistance, and refractoriness, alumina is an inert material with the highest biocompatibility currently used in the clinical field [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Al-Moameri et al [13] investigated the biological uses of alumina and found that it is quite inactive and corrosion-resistant. Alumina applies smoothly for several years and causes little tissue reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em aplicações biomédicas a AAN pode ser usada para o revestimento de metais como os utilizados em próteses para que se obtenha maior resistência à corrosão, baixo coeficiente de atrito e bioatividade (27,28). O coeficiente de atrito pode ser alterado por injeção de nanopartículas de ativos com o objetivo de aumentar a abrasividade do material.…”
Section: Aplicações Da Alumina Anódica Nanoporosaunclassified